2000
DOI: 10.1177/1077558700057001s06
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Access to Medical Care

Abstract: The authors' review of the health services literature since the release of the landmark Report of the Secretary's Task Force Report of Black and Minority Health in 1985 revealed significant differences in access to medical care by race and ethnicity within certain disease categories and types of health services. The differences are not explained by such factors as socioeconomic status (SES), insurance coverage, stage or severity of disease, comorbidities, type and availability of health care services, and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
124
1
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(140 citation statements)
references
References 74 publications
8
124
1
3
Order By: Relevance
“…The cost is highly subsidized by the Ministry of Women, Family and Community Development where it provides a RM50 (USD 14.78) subsidy for every mammography session done which usually costs RM100-RM130 (USD 29.56 to USD 38.43) per session. Commonly recognized economic barriers to mammography are often related to accessibility to mammography facilities including proximity, transportation, and child care (Powell et al, 2005;Ferrante et al, 2006); and accessibility to mammography services including insurance (Mayberry, Mili & Ofili, 2000;Royak-Schaler, et al, 2003;Morales et al, 2004;Peek & Han, 2004). Cost was the most frequently reported reasons for a reluctance to participate in clinical breast examinations or mammography screenings (Chua et al, 2005) In this study, age was a significant influence in the practice of mammogram among the participants.…”
Section: Discussionmentioning
confidence: 99%
“…The cost is highly subsidized by the Ministry of Women, Family and Community Development where it provides a RM50 (USD 14.78) subsidy for every mammography session done which usually costs RM100-RM130 (USD 29.56 to USD 38.43) per session. Commonly recognized economic barriers to mammography are often related to accessibility to mammography facilities including proximity, transportation, and child care (Powell et al, 2005;Ferrante et al, 2006); and accessibility to mammography services including insurance (Mayberry, Mili & Ofili, 2000;Royak-Schaler, et al, 2003;Morales et al, 2004;Peek & Han, 2004). Cost was the most frequently reported reasons for a reluctance to participate in clinical breast examinations or mammography screenings (Chua et al, 2005) In this study, age was a significant influence in the practice of mammogram among the participants.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the increasing racial disparity in rates of avoidable hospitalization are not clear, although numerous studies have found racial differences in the provision of health care. 14 The lack of significant racial differences in rates of avoidable hospitalization for the elderly, who are almost all covered by Medicare, suggests that insurance coverage should be considered as a possible factor in the diff erences among younger populations. Researchers need to examine whether racial differences in levels of insurance or the adequacy of coverage are creating barriers to ambulatory care that lead to more avoidable hospitalizations.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Studies have consistently found disparities in access to and utilization and quality of mental health care (1013) and other types of health services (1416). However, findings on substance abuse treatment disparities have been mixed.…”
mentioning
confidence: 99%